Strengthening Digital Legal Literacy for Church Youth: Anti-Hoax Awareness and Prevention of Online Sexual Harassment under Indonesia’s ITE Law No. 1 of 2024 - Edo Maranata Tambunan; Binsar Daniel Panjaitan; Baginta Manihuruk; Herman Fasiona Hutabarat; Erikson Damanik; Toras Pangindoan Batubara; Meylida Girsang; Khansa Khalishah; Hengki Mangiring Parulian Simarmata (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
The rapid advancement of digital technology has reshaped the behavior and communication patterns of young people, including church youth who are highly active on social media. However, the lack of digital literacy and legal awareness often leads to the spread of hoaxes, unethical online behavior, and the risk of digital sexual harassment. This Community Service Activity (PKM) titled “Strengthening Digital Legal Literacy for Church Youth: Anti-Hoax Awareness and Prevention of Online Sexual Harassment under Indonesia’s ITE Law No. 1 of 2024” was carried out at HKBP Bethesda Perumnas Mandala Church, aiming to enhance youth understanding of the ITE Law and encourage responsible social media use. The activity was conducted through an interactive seminar and discussion involving 30 participants, focusing on three core topics: understanding the ITE Law, anti-hoax education, and digital sexual harassment prevention. The results showed a significant increase in participants’ awareness of digital ethics, legal responsibility, and strategies for online safety. Participants actively engaged in discussions, demonstrating high enthusiasm and comprehension of the material. This activity proves that collaboration between universities and churches can effectively promote digital legal literacy and moral awareness among the younger generation, supporting the creation of a safe, ethical, and law-abiding digital environment.